2021
DOI: 10.1002/hbm.25710
|View full text |Cite
|
Sign up to set email alerts
|

Left parietal involvement in motion sickness susceptibility revealed by multimodal magnetic resonance imaging

Abstract: Susceptibility to motion sickness varies greatly across individuals. However, the neural mechanisms underlying this susceptibility remain largely unclear. To address this gap, the current study aimed to identify the neural correlates of motion sickness susceptibility using multimodal MRI. First, we compared resting-state functional connectivity between healthy individuals who were highly susceptible to motion sickness (N = 36) and age/sex-matched controls who showed low susceptibility (N = 36).Seed-based analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…This idea is also supported by findings from Zhang et al [105], who detected hemispheric asymmetry in car passengers experiencing motion sickness. More activity was found over the left hemisphere, particularly over visual areas (occipital lobe) and parietal regions, which is inline with studies using MRI/fMRI to study motion sickness [67,83], but also over the frontal lobe. Findings by Yamamura et al, who integrated a one sensor fNIRS device into their VR headset, also highlighted the potential for frontal lobe fNIRS to be used to detect cybersickness [100].…”
Section: Fnirs and Cybersicknesssupporting
confidence: 85%
“…This idea is also supported by findings from Zhang et al [105], who detected hemispheric asymmetry in car passengers experiencing motion sickness. More activity was found over the left hemisphere, particularly over visual areas (occipital lobe) and parietal regions, which is inline with studies using MRI/fMRI to study motion sickness [67,83], but also over the frontal lobe. Findings by Yamamura et al, who integrated a one sensor fNIRS device into their VR headset, also highlighted the potential for frontal lobe fNIRS to be used to detect cybersickness [100].…”
Section: Fnirs and Cybersicknesssupporting
confidence: 85%
“…These results suggest that the degree of sensory reweighting in the angular gyrus affects cybersickness intensity. A multimodal magnetic resonance imaging study investigated the functional connectivity related to motion sickness susceptibility 44 . Individuals who were resistant to motion sickness demonstrated greater negative functional connectivity between the left vestibular and visual cortices than those who were susceptible to motion sickness 44 .…”
Section: Discussionmentioning
confidence: 99%
“…A multimodal magnetic resonance imaging study investigated the functional connectivity related to motion sickness susceptibility 44 . Individuals who were resistant to motion sickness demonstrated greater negative functional connectivity between the left vestibular and visual cortices than those who were susceptible to motion sickness 44 . They suggested that reciprocal visual-vestibular interactions are associated with motion sickness susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The neural mechanisms underlying traditional motion sickness resistance or susceptibility remain largely unclear, not to mention emerging visually-induced motion sickness, like VRMS in this study. A recent resting-state functional magnetic resonance imaging (fMRI) study suggests that there may be a left parietal dominance in susceptibility to motion sickness [32]. The authors found that motion sickness-resistant individuals have greater negative functional connectivity between the left PIC and primary visual cortex area while motion sickness-susceptible individuals show co-activation of the two regions, meaning that motion sickness-resistant individuals may have reduced visual-vestibular mismatch through better reciprocal visual-vestibular interactions (or reweighting in our view, see below) while motion sicknesssusceptible individuals have poorer visual-vestibular interactions thus may lead to fierce sensory conflict.…”
Section: The Source Of Discovered Theta Pattern (Left Pic?)mentioning
confidence: 99%